Tahap kesediaan guru menggunakan teknologi dalam Pengajaran dan Pembelajaran (P&P) di sekolah menengah kebangsaan - Wahaida, Wahi (2008)
This study is a survey done on teachers of geography at sekolah menengah kebangsaan, daerah Timur Laut, Penang. The aim of this study is to look at teachers' degree of readiness in using technology for teaching and learning with regards to knowledge, competency, interest, attitude and self effectiveness. Furthermore, this study intends to find out the differences of teachers' readiness according to age and gender. 104 sets of questionnaires were distributed and completed by all respondents. Each set consists of seven sections comprising 92 items of four Likert scale in order to obtain the responses for independent and dependent variables. 12 hypothesis were formulated for this study. Data gathered were analysed using Statistical Package for Social Science (SPSS) Release 15.0 for Windows to establish descriptive and inferential statistics. Descriptive analysis was conducted using the techniques of frequency distributions, variances and means to illustrate respondents' level of knowledge, competency, interest, attitude and self effectiveness. Whilst inferential statistics was employed to test the hypothesis through the t-test. Findings from the t-test indicate insignificant differences in terms of the Geography teachers' degree of readiness in using technology for teaching and learning in relations to knowledge, competency, interest, attitude and self effectiveness. The findings also reveal moderate level of the teachers' readiness for all five characteristics.